Level of compliance with the use of the dosimeter as a standard of radiological protection of radiology students - Barros-Astudillo , Teodoro (2021)
AbstractIntroduction. The Pan American Health Organization ponders the importance of protection and safety against radiation and radiological emergencies, considering benefits and risks for the uses of radiation in industrial, medical and research applications. The use of radiation also has potential risks to the health of patients, workers (including health personnel), the public, and the environment. The Central University of Ecuador, through the Faculty of Medical Sciences, has the Radiology Career, which trains professionals in this area, with competencies for diagnostic studies, promotion, prevention and research for the benefit of people in a situation of illness; In this context, undergraduate students who carry out pre-professional training practices in health care units, and who are continuously exposed to risks due to ionizing radiation, are enrolled. Objective. Determine the level of compliance with the use of the dosimeter as a radiation protection standard in imaging. Material and methods. The study is descriptive, observational, cross-sectional and analytical. The sample is 58 undergraduate students (seventh and eighth semesters) randomly selected with a 95% confidence level, in the year 2019. Documentary analysis and survey (students and Heads of Radiology Service) were applied. The last three results of the dosimetry tests were analyzed. The reliability statistic of the instrument with Cronbach's Alpha is high (0.833). The data was processed through EXCEL and PSPP. Statistical analyzes were descriptive and a contingency table with Pearson's Chi2 test of independence. Results. The students, men and women, do not regularly use the dosimeter, in the three measurements. By sex, there is a significant difference according to Chi2, in the first measurement and second measurement (p<0.05). In the third measurement, there are no significant differences, but the two groups also do not regularly use the dosimeter. Limitation: The studied sample does not correspond to all the students of the radiology career, prioritizing the last years of training. Conclusions. There is non-compliance in the use of the dosimeter as a radiation protection standard, which increases the chances of health risks for students who carry out pre-professional training practices.